Interleukin-8. A corneal factor that induces neovascularization. - Strieter, R. M. (1992)
A rabbit corneal pocket model was used to demonstrate that physiologic concentrations of human recombinant (r) IL-8 may induce corneal neovascularization. Computer-assisted analysis of sequential fluorescein angiograms showed that rIL-8 doses ranging from 2 to 40 ng/cornea (P = 0.01), but not high dose rIL-8 (400 ng/cornea), results in neovascularization within 14 days. Repeat fluorescein angiograms 6 weeks after placing angiogenic doses of rIL-8 demonstrated significant regression (P = 0.01) of the vascularity present at 2 weeks, suggesting that IL-8 angiogenesis undergoes dynamic modulation similar to that normally seen in wound healing. To our knowledge, this is the first study showing an angiogenic role for IL-8, a finding that emphasizes the interplay between inflammation and wound healing. Our results imply that corneal-derived IL-8 may be important in corneal neovascularization, in particular, and that IL-8 may modulate wound healing in general. Finally, these results raise the possibility that corneal-derived cytokines, such as IL-8, may obfuscate the effects of agents tested in experimental corneal pocket models.